Preservation of motor skill learning in patients with multiple sclerosis - Tomassini, V; Johansen-Berg, H; Leonardi, L; Paixão, L; Jbabdi, S; Palace, J; Pozzilli, C; Matthews, P (SAGE Publications, 2011)
Background: Several studies have demonstrated benefits of rehabilitation in multiple sclerosis (MS). However, the neuroscientific foundations for rehabilitation in MS are poorly established. Objectives: As rehabilitation and motor learning share similar mechanisms of brain plasticity, we test whether the dynamics of skill learning are preserved in MS patients relative to controls. Methods: MS patients and controls learned a repeating sequence of hand movements and were assessed for short-term learning. Long-term learning was tested in another cohort of patients and controls practising the same sequence daily for two weeks. Results: Despite differences in baseline performance, the dynamics and extent of improvements were comparable between MS and control groups for both the short- and long-term learning. Even the most severely damaged patients were capable of performance improvements of similar magnitude to that seen in controls. After one week of training patients performed as well as the controls at baseline. Conclusions: Mechanisms for short- and long-term plasticity may compensate for impaired functional connectivity in MS to mediate behavioural improvements. Future studies are needed to define the neurobiological substrates of this plasticity and the extent to which mechanisms of plasticity in patients may be distinct from those used for motor learning in controls.